THE INFLUENCE OF INCENTIVES, SERVANT LEADERSHIP, ANDORGANIZATIONAL CULTURE ON NURSES’ PERFORMANCE WITH WORK STRESS AS AN INTERVENING VARIABLE - Yanti Fitriani Panjaitan; Syaifuddin Syaifuddin; Salman Faris; Nagian Toni; Elly Romy (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This study aims to analyze the influence of incentives, servant leadership, and organizational culture on nurses’ performance with work stress as an intervening variable at Delima General Hospital Medan. The population consisted of 39 nurses; therefore, a saturated sampling technique was applied. Data were collected using questionnaires and documentation, then analyzed with t-tests, Sobel test, and path analysis using SPSS 25. The findings revealed: (1) incentives positively affect work stress; (2) servant leadership negatively affects work stress; (3) organizational culture positively affects work stress; (4) incentives and servant leadership have a positive and significant effect on performance; (5) organizational culture has a negative and insignificant effect on performance; (6) work stress has a positive and significant effect on performance; (7) there is no effect of incentives and servant leadership on performance through work stress; (8) organizational culture influences performance through work stress as an intervening variable.